On the problem of simile configurations - Altavista, Carlos Alberto (1965)
On the validity of the vectorial formula P = λQ + R in regard to a special problem of homographic solutions of the three-body problem with law of attraction proportional to the inverse of the cube of the mutual distances between the masses.